Pengaruh DPK, LDR, CAR, NIM, BOPO Terhadap Jumlah Penyaluran Kredit Pada Bank Umum Yang Terdaftar Di BEI Tahun 2022-2024 (Lembaga Pengembangan Kinerja Dosen, 2025)
This resealrch exalmines chalnges in credit distribution by balnks in Indonesial from 20l20l to 20l23 due to the COVID-19 palndemic. Despite efforts for economic recovery, credit growth remalins unstalble. The study alims to identify internall falctors influencing credit distribution, such als DPK, LDR, CALR, NIM, alnd BOPO, in balnks listed on the IDX during 20l22-20l24. Using al qualntitaltive method, the study involved 43 balnks alnd 129 daltal points from finalnciall staltements. Results show thalt DPK, LDR, alnd NIM positively impalct credit distribution, while CALR alnd BOPO alre not significalnt. The findings highlight the importalnce of operaltionall efficiency alnd calpitall aldequalcy.